Characterization of thermophilic bacteria from Ie Seum Hot Springs, Aceh Besar, Indonesia as producers of protease enzyme - ELITA SABARIA; YEKKI YASMIN; YULIA S. ISMAIL; MOHAMMAD A. BESSANIA; ISNAINI PUTRI; LENNI FITRI (Society for Indonesian Biodiversity, 2024)
Abstract. Sabaria E, Yasmin Y, Ismail YS, Bessania MA, Putri I, Fitri L. 2024. Characterization of thermophilic bacteria from Ie Seum Hot Springs, Aceh Besar, Indonesia as producers of protease enzyme. Biodiversitas 25: 1867-1874. Thermophilic bacteria are microorganisms that can survive in high-temperature environments exceeding 75°C. The Ie Seum Hot Springs in Aceh Besar, Indonesia are known to be a place where these thermophilic bacteria inhabit. In such extreme conditions, proteins and enzymes are often denatured, making these bacteria of interest due to their ability to adapt and produce enzymes such as proteases. Proteases are called proteolytic enzymes that can be applied both in the economic and medical fields. This study aimed to isolate and identify thermophilic bacteria species that have the highest potential for protease production in Ie Seum Hot Spring, Aceh Besar by analyzing the 16S rRNA gene and characterizing them using biochemical tests. Based on the result, seven thermophilic bacterial isolates, namely BT1, BT2, BT3, BT4, BT5, BT6, and BT7 were obtained, each showing different colony characteristics. The biochemical tests also revealed differences metabolic activity of each isolate. Of these isolates, BT4 exhibited the highest proteolytic index (4.65). Additionally, the 16S rRNA gene sequence analysis showed that the BT4 strain belongs to the genus Bacillus and has high similarities to Bacillus sp., B. licheniformis and B. sonorensis. These findings suggest that BT4 has significant potential as a source of thermophilic protease enzymes.